Atopic Dermatitis in the Elderly Population - Martina Maurelli; Andrea Chiricozzi; Ketty Peris; Paolo Gisondi; Giampiero Girolomoni (Medical Journals Sweden, 2023)
Atopic dermatitis is a common inflammatory disease with a chronic and relapsing course. Although considered a childhood disease, it is now evident that atopic dermatitis is also common in adulthood and in the elderly population. Atopic dermatitis typically manifests with bilateral and symmetrical eczematous lesions on the face, trunk and skin folds. Itch is invariably present and may be very severe, markedly  affecting daily life and sleep. In older adults, atopic dermatitis may have a high level of impact on quality of life, frequently burdening an already complex comorbid situation. The full assessment of disease burden (localizations, itch severity, sleep alterations, impact on quality of life, disease history, comorbidities) is crucial to identify the most appropriate treatment. In many cases, moderate-to-severe atopic dermatitis in the elderly population can be successfully and safely treated with biological agents inhibiting the interleukin-4/-13 pathway, whereas the use of Janus kinase inhibitors may pose concerns about the safety profile.